Theology as translation: Ibn Taymiyya’s Fatwa permitting theology and its reception into his averting the conflict between reason and revealed tradition (Dar' Ta'aruḍ al-'Aql waʾl-Naql) - Hoover, Jon; Mahajneh, Marwan Abu Ghazaleh (Wiley, 2018)
The Ḥanbalī jurist Ibn Taymiyya (d. 728/1328) wrote his famous tome Darʾ Taʿāruḍ al-ʿAql waʾl-Naql (Averting the Conflict between Reason and Revealed Tradition) in Damascus sometime after 713/1313 to critique the “universal rule” (qānūn kullī) of the Ashʿarī kalām theologian Fakhr al-Dīn al-Rāzī (d. 606/1210).2 According to al-Rāzī’s rule, precedence must be given to reason when reason and revelation conflict, and, when reason contradicts the plain sense of a revealed text, that sense must be either reinterpreted to accord with reason or delegated to God and given no further reflection.3 Ibn Taymiyya rejects al-Rāzī’s rule with 44 considerations or arguments (wujūh) of widely varying length to make the claim that there is in fact no conflict between reason and revealed tradition. Reason properly understood and the texts of revelation are in complete accord.